Diastereo- and enantioselective intramolecular 1, 6-C–H insertion reactions of α-diazo esters catalyzed by chiral dirhodium(II) carboxylates. Issue 11 (11th March 2015) - Ito, Motoki; Kondo, Yuji; Nambu, Hisanori; Anada, Masahiro; Takeda, Koji; Hashimoto, Shunichi
Graphical abstract: Abstract: The first catalytic asymmetric intramolecular 1, 6-C–H insertion reaction of α-diazo esters is described. With dirhodium(II) tetrakis[ N -phthaloyl-( S )- tert -leucinate], Rh2 ( S -PTTL)4, the C–H insertion proceeded in a chemoselective manner to give 2-alkenyltetrahydropyran-3-carboxylates with up to 95% ee and perfect cis diastereoselectivity.